The effect of maternal alcohol and drug abuse on first trimester screening analytes: a retrospective cohort study - Anni Lehikoinen; Raimo Voutilainen; Jarkko Romppanen; Seppo Heinonen (BMC, 2020)
Abstract Background The purpose of this study was to determine whether first trimester trisomy screening (FTS) parameters are affected by alcohol and drug use. Methods A routine combined FTS including measurements of maternal serum levels of free β-human chorionic gonadotropin subunit (free β-hCG) and pregnancy-associated plasma protein A (PAPP-A) were measured at 9-11 weeks of gestation, and fetal nuchal translucency thickness (NTT) at 11-13 weeks of gestation. In total 544 women with singleton pregnancies [71 alcohol and drug abusers, 88 smokers, 168 non-smokers delivering a small for gestational age (SGA) child, and 217 unexposed control women] were assessed. Results Free β-hCG levels were higher in alcohol and drug abusing than in unexposed pregnant women [mean 1.5 vs. 1.2 multiples of medians (MoM); P = 0.013]. However, stepwise multiple linear regression analyses suggested that smoking could explain increased free β-hCG. Additionally, we observed lower PAPP-A levels in the smoking mothers (0.9 vs. 1.2 MoM; P = 0.045) and in those giving birth to an SGA child compared to the controls (1.1 vs.. 1.2 MoM; P < 0.001). Fetal NTT did not differ significantly between any of the groups. Conclusions The present study shows increased free β-hCG levels in alcohol and drug abusers, but maternal smoking may explain the result. Maternal serum PAPP-A levels were lower in smoking than non-smoking mothers, and in mothers delivering an SGA child. However, FTS parameters (PAPP-A, free β-hCG and NTT) seem not to be applicable for the use as alcohol biomarkers because of their clear overlap between alcohol abusers and healthy controls.